A problematic animal fossil from the early Cambrian Hetang Formation, South China—A reply. (November 2019) - Tang, Qing; Hu, Jie; Xie, Guwei; Yuan, Xunlai; Wan, Bin; Zhou, Chuanming; Dong, Xu; Cao, Guohua; Lieberman, Bruce S.; Leys, Sally P.; Xiao, Shuhai
Abstract: We recently reported Cambrowania ovata Tang and Xiao in Tang et al., 2019, from the early Cambrian Hetang Formation in South China and interpreted it as a problematic animal fossil, possibly related to either sponges or bivalved arthropods (Tang et al., 2019). Slater and Budd (2019) contested our taxonomic identification and phylogenetic interpretation; instead, they claimed that Cambrowania ovata is a large acritarch referable to morphotaxon Leiosphaeridia Eisenack, 1958, and thus is not an animal. Here we refute their criticisms, clarify the differences between Cambrowania and Leiosphaeridia and other acritarchs, and reiterate why an animal affinity for Cambrowania cannot be ruled out.